An architectural investigation into the provision of refugee accommodation - Lizancos, P; Zas, E (Refugee Studies Centre, University of Oxford, 2017)
When challenged to investigate accommodation options for refugees in their city, architecture students found that there are simple and plausible architectural answers for the integration of refugees in medium-sized European cities such as A Coruña.